TRANSNATIONAL ISLAMIC MOVEMENTS IN INDONESIA - Husnul Hidayah; Suadi Sa’ad; Andi Rosa (Profetika: Jurnal Studi Islam, 2024)
Transnational Islamic Movement is a new vocabulary in academic view. This movement tends to focus on ideological ideas that side with Muslims all over the world. The main factor in the emergence of the Islamic Movement in Indonesia is because Indonesia is a country with the most adherents of Islam in the world. This study reviews the Transnational Islamic Movement in Indonesia. It aims to find out the history of the Transnational Islamic Movement and whatever groups exist in Indonesia. The type of this research is historical research. In this research, the authors review the premises and practice of the historical method to understand how it came to be. The result is the discovery of Islamic groups such as (1) Wahhabism, (2) Ikhwanul Muslimin, (3) Hizbut Tahrir, (4) Jihadi, (5) Da'wah Salafi and Sururi, (6) Tablighi Jamaat, and (7) Syiah.